2021
DOI: 10.1021/jacs.1c10327
|View full text |Cite
|
Sign up to set email alerts
|

Merging Supramolecular and Covalent Helical Polymers: Four Helices Within a Single Scaffold

Abstract: Supramolecular and covalent polymers share multiple structural effects such as chiral amplification, helical inversion, sergeants and soldiers, or majority rules, among others. These features are related to the axial helical structure found in both types of materials, which are responsible for their properties. Herein a novel material combining information and characteristics from both fields of helical polymers, supramolecular (oligo( p -phenyleneethynylene) (OPE)) and covalent (poly(ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 83 publications
1
16
0
Order By: Relevance
“…To distinguish the origin of bisignate CD signals in these two negative states, we further performed ltration experiments. 32 As shown in Fig. S12b, † the CD signal and UV-vis absorption of PAzo-L-3 in DCE solution before and aer ltration were basically unchanged.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…To distinguish the origin of bisignate CD signals in these two negative states, we further performed ltration experiments. 32 As shown in Fig. S12b, † the CD signal and UV-vis absorption of PAzo-L-3 in DCE solution before and aer ltration were basically unchanged.…”
Section: Resultsmentioning
confidence: 87%
“…Although the transition between the secondary chirality and tertiary chirality in polymers plays an important role in nature, the interactive connection of the above two different hierarchical chiralities has been rarely studied. The control of chirality inversion in polymer systems mainly focuses on the regulation of the helical conformation of the main-chain conjugated polymers in a dissolved state [29][30][31][32][33] or supramolecular chirality of polymer assemblies in an aggregated state. 34,35 Malashkevich et al reported that macromolecular-to-supramolecular helicity inversion existed in cartilage oligomeric matrix proteins.…”
Section: Introductionmentioning
confidence: 99%
“… 19 , 20 , 21 To be functional, these helical polymers must adopt macromolecular helical structures with screw sense excess. This can be achieved using supramolecular interactions with different external stimuli, 22 , 23 by controlling the conformational composition of the pendant groups 24 , 25 , 26 , 27 or by means of different chiral communication mechanism like Sergeants and Soldiers Effect, 28 , 29 , 30 , 31 Majority Rules, 32 , 33 Chiral Coalition, 34 Chiral Harvesting, 35 , 36 , 37 or Chiral Teleinduction 38 among others.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this obstacle, it is necessary to explore other helical macromolecules to decorate MNPs. In this sense, stimuli-responsive synthetic helical polymers 12–48 are excellent candidates to prepare helical polymer-MNP nanocomposites where the two chiralities of the helix can be explored in different fields. From the literature, it is known that the main limitation of the use of dynamic helical polymers as coating agents to prepare helical polymer-MNP nanocomposites is the functional group used to link the macromolecule to the metal nanoparticle.…”
Section: Introductionmentioning
confidence: 99%